Effect of susceptor and mold material on microstructure of in-situ microwave casts of Al-Zn-Mg alloy. (5th October 2017) - Mishra, Radha Raman; Sharma, Apurbba Kumar
Abstract: In-situ microwave casting is a novel technique; it is based on the principles of microwave hybrid heating. The dynamics of the process and the cast quality are significantly influenced by the materials used in the microwave irradiation. In the present work, role of susceptor and mold on exposure time, melting time, mold preheating and cast properties is studied. Physics of the process in the context of exposure time and mold materials is discussed. The aluminum alloy 7039 casts were developed in ambient atmosphere inside an applicator using microwaves at 2.45 GHz and 1400 W. Charge was hybrid heated using susceptors – SiC and ceramic crucible to melt and cast in-situ in the preplaced alumina and graphite molds. Characterization reveals that grain structures of the casts were influenced by mold preheating and mold material. Finer grains with higher micro-pores were observed in the casts developed in alumina mold with SiC susceptor. The casts contain MgZn2, Mg2 Si, Al3 Fe and Al8 Fe2 Si as intermetallics; however, their distribution and size depend upon the cooling pattern of the melt. Microindentation hardness of the casts developed in alumina mold with SiC susceptor was observed to be the highest (146 ± 10 HV) among the developed casts. Graphical abstract: Highlights: In-situ microwave casts are developed using different susceptors and mold materials. Thermal characteristics of susceptor and charge are analyzed in the context of exposure time. Roles of mold material and exposure time on development of in-situ casts are discussed. Microstructural characterizations of the developed in-situ casts are presented.